Oncological right hemicolectomy in a trimodal comparison: open surgery versus laparoscopic procedures with extra- and intracorporeal anastomosis technique - Kerber, Kerstin M.; Hetjens, Svetlana; Reißfelder, Christoph; Herrle, Florian; Seyfried, Steffen (International journal of colorectal disease, 2024)
This study aimed to investigate the surgical short- and mid-term outcomes, as well as the impact on quality of life and recovery, following oncological right hemicolectomy. To accomplish this, three patient cohorts were examined, which included laparotomy OA), laparoscopy with intracorporeal anastomosis (LIA), and laparoscopy with extracorporeal anastomosis (LEA). Our hypothesis was that the group undergoing intracorporeal anastomosis would demonstrate superior outcomes compared to the other cohorts.